An Exploratory Data Analysis from Ovine and Bovine RNA-Seq Identifies Pathways and Key Genes Related to Cervical Dilatation - Gonçalves, Joedson Dantas [UNESP]; Ferraz, José Bento Sterman; Meirelles, Flávio Vieira; Nociti, Ricardo Perecin; Oliveira, Maria Emilia Franco [UNESP] (MDPI, 2023)
The present study developed a review and exploration of data in public and already validated repositories. The main objective was to identify the pathways involved in ruminants’ cervical dilatation, which are conserved between cattle and sheep in the follicular and luteal phases of the reproductive cycle. In cattle, 1961 genes were more differentially expressed in the follicular phase and 1560 in the luteal phase. An amount of 24 genes were considered exclusively expressed from these. A total of 18 genes were in the follicular phase and 6 genes were in the luteal phase. In sheep, 2126 genes were more differentially expressed in the follicular phase and 2469 genes were more differentially expressed in the luteal phase. Hoxb genes were identified in both species and are correlated with the PI3K/Akt pathway. PI3K/Akt was also found in both cattle and sheep, appearing prominently in the follicular and luteal phases of both species. Our analyses have pointed out that the PI3K/Akt pathway and the Hoxb genes appear in prominence in modulating mechanisms that involve estrus alterations in the cervix. PI3K/Akt appears to be an important pathway in the cervical relaxation process.
Keywords: cattle; cervix; reproduction; sheep; transcriptome